A Life Disrupted: Perspectives on Track 2 MAID from Persons Living with Chronic Illness - Pesut, Barbara; Thorne, Sally; Variath, Caroline; Hall, Margaret; Schiller, Catharine; Sharp, Helen; Wiebe, Glendon; Robertson, W.; McKenzie, Michael; Plewes, Laurel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Background: In 2021, Canada extended Medical Assistance in Dying (MAID) to persons whose natural death is not reasonably foreseeable, referred to as Track 2 MAID. The purpose of this study was to develop a better understanding of best practices for Track 2 MAID from the perspectives of those living with an illness, disease, or disability that could potentially make them eligible for MAID. Methods: This was a qualitative interview study using the principles of Interpretive Description. Seven participants were interviewed three times over a period of 3-6 weeks. Findings: Participants described prolonged and complex illness trajectories that resulted in suffering from loss, stigma, and iatrogenic harm. The expertise they had developed over years of living with their condition and the challenges they had experienced in healthcare informed their perspectives about MAID care. Participants highlighted essential expertise needed for Track 2 assessors to provide compassionate, trauma-informed care. Participants recognized the need for time to achieve a holistic understanding of each applicant’s experience, consequent suffering, attempts to relieve that suffering, and to develop a picture of decline over time. Participants were troubled by perceived tension between autonomy and the role of the social determinants of health in determinations of eligibility for MAID. Discussion: Overall, participants described the necessity of a partnered approach to Track 2 MAID assessment. Although participants considered the individual autonomy of others as more important than their personal views, they expressed grave concerns about the potential for inadequate health and social care systems to influence requests for MAID.